Association of Serum Homocysteine with Gestational Diabetes Mellitus (GDM): A Case-Control Study - Nessa, Meherun; Das, Tripti Rani; Jahan, Esrat; Md Munim Ur Rahman Khan (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Gestational diabetes mellitus (GDM) is associated with an increased risk of maternal and fetal mortality and morbidity. There is an increasing trend in the prevalence of GDM in Bangladesh. The role of homocysteine (Hcy) as an independent risk factor of GDM has not been extensively studied. The aim of this study was to evaluate the association of serum homocysteine levels in gestationaldiabetes mellitus. It was a case-control study among pregnant women attending the inpatient and outpatient departments of Obstetrics and Gynecology,BSMMU, Shahbag Dhaka, from April 2020 to March 2021. A total of 80 singleton pregnant women between 18-35 years of age were included in this study in their 24-40 weeks of gestation. Among them, 40 diagnosed women with GDM were considered as the cases and the rest of the 40 matched healthy pregnant women were selected as controls matching for age and gestational age.The overall average Hcy levels in the cases and controls were 5.48±1.3 μmol/L and 4.06±0.98 μmol/L, respectively. Both in the late second trimester and the third-trimester serum Hcy levels were significantly higher in the GDM cases than non-GDM healthy pregnant women (p<0.05). Considering Hcy level of 6.38 μmol/L as the cut-off value, GDM was 4.75 times more likely in pregnant women with elevated serum Hcy level (≥6.38) than those with < 6.38 μmol/L (OR=4.75; 95% CI = 0.941-23.985). There was a significant positive correlation of serum Hcy level with both fasting blood sugar level (r = +0.600, p<0.001) and 2 hrs after 75g glucose level (r = +0.438, p<0.001). Elevated level of serum homocysteine was found associated with GDM. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):32-37